IMPLEMENTASI PEMBELAJARAN ANAK USIA DINI BERBASIS BUDAYA LOKAL DI PAUD FULL DAY SCHOOL - Muzakki Muzakki; Puji Yanti Fauziah (Universitas Negeri Yogyakarta, 2015)
The objectives of this study are to describe the implementation of local wisdom in full day early childhood school. This study applies qualitative research with a single-case study approach. This research is done in Fairuz Aqila institution in Kalasan, Sleman which is an early childhood education center in Daerah Istimewa Yogyakarta which applies local wisdom. The data of the research were collected through observation, interview, documentation, and triangulation. The results of the study showed that the implementation of full day early childhood school based on local wisdom is applied by identifying the children's need,  determining the topic of learning, arranging lesson plan which includes program planning of annual,weekly, and daily activity programs, integrating local wisdom into learning process through the basic, main, and day care activity, applying learning assessment by means of observation, anecdote, and check list. The elements of local wisdom which are acknowledged are Javanese culture norms, religious system, traditional games, traditional foods, Javanese traditional dance, Javanese language, livelihood system, Javanese songs, traditional music instruments, and folktales.